2013
DOI: 10.2298/vsp110505015d
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of a modified balloon dilatation in the treatment of patients with achalasia

Abstract: Modified balloon dilatation can be recommended for initial method in achalasia treatment due to high efficacy, easy performance in daily hospital while complications are in standard range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The gender of patient was not associated with failure of dilatation and the same appears in most studies 4,5,8 .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The gender of patient was not associated with failure of dilatation and the same appears in most studies 4,5,8 .…”
Section: Discussionsupporting
confidence: 75%
“…Modified BD was performed with Rigiflex balloon dilator (Boston Scientific USA) without sedation up to the pain threshold of patients 4 . In 44 patients one BD was performed and in 8 patients two BD were done due to relapse of disease (7) and dilatation failure (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…748 records were screened, and 88 full-length articles were assessed. Sixty-six studies 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 were included in the final analysis, four of which directly compared outcomes of POEM to PD 32 35 36 38 . A total of 29 studies reported on the outcomes of POEM 24 …”
Section: Resultsmentioning
confidence: 99%
“…Balloon dilatation implicates balloon inflation at the level of esophageal and gastric junction with resulting rupture of muscle fibers, with preservation of esophageal mucosa. Success rate for this procedure is 80%, according to the study by Doder et al [10] and esophageal perforation is noted in 5% of patients, which requires urgent surgical intervention [11]. Surgical method of choice is Heller's myotomy with partial fundoplication.…”
Section: Discussionmentioning
confidence: 99%